GENDER COGNITION IN RELIGIOUS DISCOURSE: A STUDY OF FRAMING IN THEMATIC HOLY KORAN INTERPRETATION - Anshori, Dadang S. (Universitas Pendidikan Indonesia, 2016)
The study is aimed at describing gender cognition phenomenon in religious discourse in thematic interpretation (tafsir) of the Holy Koran published by the Ministry of Religious Affairs of the Republic of Indonesia. Each interpretation book as a written discourse is different from each other due to author’s cognition frame. This study employs a constructive qualitative approach with technical framing analysis. The data are language data (religious text) that are obtainable from thematic interpretation of the Koran of the Ministry of Religious Affairs of the Republic of Indonesia. Data analysis was performed on the following topics: the origins of the creation of men and women, women's leadership, women and inheritance rights, women and ownership, and women's testimony. The research findings show: (1) The lingual and religious discourse containing gender cognition are present in the forms of words, phrases, and sentences. The lingual form of religious discourse is related to the meaning of technical vocabulary that contains appropriate understanding of the discourse topic. (2) Discourse representing gender cognition is found on three topics: women leadership (nation leadership), waris (inheritance), and women’s testimony. In terms of inheritance and women’s testimony, this interpretation refers to conditions that are explicitly stated in the Holy Koran. Meanwhile, this interpretation views leadership of the nation as more worthy to be given to men than women. book looks is more worthy of leadership in the countries was given to men than women.